Navigating access to Indonesia’s National Health Insurance: determinants and barriers among informal sector workers in West Sumatra - Roza, Shelvy Haria; Sari, Ayulia Fardila (BKM Public Health and Community Medicine, 2025)
Purpose: This study aimed to identify the factors that influence and barriers to the utilization of JKN for informal sector workers in West Sumatra Province. Methods: The study employed a quantitative cross-sectional design. The data used are secondary data from the 2022 Susenas. The population of this study consisted of informal workers aged 15-64 years, comprising approximately 10,909 people. The sample consisted of informal workers with health complaints and a history of outpatient care, specifically 4,606 individuals. This study uses JKN utilization as the dependent variable. Meanwhile, there are several independent variables: JKN ownership, age, gender, economic status, region of residence, education, and employment. Data were analyzed using the STATA application in univariate, bivariate analyses with the Chi-Squared test, and multivariate analyses with binary logistic regression. Results: The results showed that most respondents (59.12%) did not use JKN due to various barriers, including a preference for self-medication (76%), lack of knowledge on how to use JKN (10%), and difficulties with procedures (5%). The productive age group was significantly more likely to use JKN (OR 4.653; 95% CI 1.837 - 11.784). The poor are more likely to use JKN than those in the lower-middle income groups (OR 6.955; 95% CI 1.444-33.497). Conclusion: The wealth status and age had a significant influence on the use of JKN. Expand access to affordable health services for low-income individuals and older adults. Barriers to using JKN are practical and require policy interventions. Insurance subsidies, development of mobile-based services, and strategies for the dissemination of information and benefits of JKN.